2021
DOI: 10.22454/fammed.2021.546572
|View full text |Cite
|
Sign up to set email alerts
|

Resident Remediation in Family Medicine Residency Programs: A CERA Survey of Program Directors

Abstract: Background and Objectives: Identifying underperforming residents and helping them become fully competent physicians is an important faculty responsibility. The process to identify and remediate these learners varies greatly between programs. The objective of this study was to evaluate the remediation landscape in family medicine residency programs by investigating resident remediation characteristics, tools to improve the process, and remediation challenges. Methods: This study analyzed responses from the Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…5 ADHD was the most prevalent disability in their sample. Nouri and colleagues surveyed a national sample of practicing physicians and found that of those with a documented disability (3% of the total sample), 10.4% endorsed having an ADHD diagnosis. Physicians with disabilities are more likely than their peers without disabilities to face discrimination and harassment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ADHD was the most prevalent disability in their sample. Nouri and colleagues surveyed a national sample of practicing physicians and found that of those with a documented disability (3% of the total sample), 10.4% endorsed having an ADHD diagnosis. Physicians with disabilities are more likely than their peers without disabilities to face discrimination and harassment.…”
Section: Introductionmentioning
confidence: 99%
“…8 Because stakeholders in medical education perceive "accountability and conscientiousness" as a subcompetency of professionalism, 9 concerns in these areas may be observed as professionalism lapses. Given that professionalism is the most common reason for remediation in family medicine residency programs, 10 residents with ADHD who do not request accommodation may face remediation for concerns about professionalism.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of US family medicine residency directors found that 74.3% (191 of 257) reported that their program offers international and/or domestic global health experiences (Hernandez et al, 2016). In almost half of these programs (47.5%), residents paid for their own international global health-related expenses; 8.8% and 6.6% of these residency programs paid for the international trips outright or via special grants, respectively (Hernandez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A survey of US family medicine residency directors found that 74.3% (191 of 257) reported that their program offers international and/or domestic global health experiences (Hernandez et al, 2016). In almost half of these programs (47.5%), residents paid for their own international global health-related expenses; 8.8% and 6.6% of these residency programs paid for the international trips outright or via special grants, respectively (Hernandez et al, 2016). According to a survey of fellowship directors and designees, the most common single-specialty global health fellowship programs in North America were in emergency medicine (23/50) and family medicine (22/50) (Evensen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2,6,8,[17][18][19][20] In these studies, educator perspectives are privileged, with several reports describing PD perspectives of remediation. [21][22][23][24][25][26][27][28] Learner underperformance, from the perspective of physician educators, was perceived as an inability or unwillingness to engage in programmatic learning. 27 Despite resident physicians being key stakeholders in their learning and performance, there is little published from the remediated learner's perspective.…”
Section: Introductionmentioning
confidence: 99%